NEOLOGISMS AS A LINGUISTIC UNIT AND THE INTERPRETATION OF SUCH WORDS THAT ENTERED THE UZBEK LANGUAGE - Ahmedov, Oybek Saporbayevich (Журнал иностранных языков и лингвистики, 2023)
Language is the wealth of society, it enables the interaction of society members increases, gathers and informs about all the events and phenomena that occur in a person's material and spiritual life. Language in the same sense, it is formed and exists over centuries. Language in the reforms carried out in the field of spirituality in our country special attention is being paid to the problems of the state language, in particular not for nothing.